The Development of National and International Legislation in the Field of Countering the Financing of Terrorist and Extremist Activities - MURATZHAN, Zarina; BISHMANOV, Kakimzhan Muratzhanovich; DILBARKHANOVA, Zhanat Rakhimzhanovna (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
This article discusses the legal aspects of countering the financing of terrorism and extremism at the national and international levels. The economic basis for the activities of terrorist and extremist organizations is money, which in many cases is received from legalized shadow incomes. Therefore, the legalization of shadow incomes and the financing of terrorism and extremism are inseparable in the legislation of many countries and international law. This article discusses some national characteristics and international legal experience in countering money laundering and the financing of terrorism and extremism. The purpose of the present work is to analyze the possibilities of applying global experience in countering the activities of terrorist and extremist organizations by suppressing their financing and making it more difficult. The authors have examined legal acts and the opinions of researchers suggesting various methods of countering the financing of terrorism. The analysis of the above materials allowed the authors to conclude the need to use international experience to improve the legal framework for countering the financing of terrorism and extremism in Kazakhstan.